Isolation and Characterization of Potential Lactic Acid Producing Bacteria from Fermented Fruit Juice - Wah Wah Than; Saw Sandar Maw; Reemon Htun (Universitas Gadjah Mada, 2022)
Lactobacillus species are used as probiotics to inhibit human pathogens because of their ability to produce antimicrobial substances. However, when different kinds of antibiotics are used, the antibiotic resistance of drug-resistant bacteria increases. In this study, lactic acid-producing bacteria with antimicrobial activity were isolated and used as probiotics to inhibit six human pathogens, namely Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Bacillus cereus, Salmonella typhi, and Shigella boydii. Nine bacterial isolates were obtained from the crude juice of sugar cane (Saccharum officinarum), strawberry (Fragaria ananassa), and fruit pulp of palm (Borassus flabellifer). Among them, three bacterial isolates (S1, SC, and PP) produced acid and clear zones around the colonies on Glucose Yeast Extract media supplemented with calcium carbonate (GYC). These three bacterial strains were then identified on the basis of colony morphology and using different biochemical tests. 16s rRNA sequencing identified the indigenous lactic acid-producing bacteria S1 as Lactobacillus plantarum and both isolates (SC and PP) as Leuconostoc mesenteroides. L. plantarum (S1) showed the best inhibition zone (12 mm) on pathogens S. aureus, P. aeruginosa, and E. coli. Therefore, these lactic acid-producing bacteria isolated from various fermented fruit juices in Myanmar shows potential for development as probiotics.